Authenticity and integrity of digital mammography images. - Zhou, X.Q.
Data security becomes more and more important in telemammography which uses a public high-speed wide area network connecting the examination site with the mammography expert center. Generally, security is characterized in terms of privacy, authenticity and integrity of digital data. Privacy is a network access issue and is not considered in this paper. The authors present a method, authenticity and integrity of digital mammography, here which can meet the requirements of authenticity and integrity for mammography image (IM) transmission. The authenticity and integrity for mammography (AIDM) consists of the following four modules. (1) Image preprocessing: To segment breast pixels from background and extract patient information from digital imaging and communication in medicine (DICOM) image header. (2) Image hashing: To compute an image hash value of the mammogram using the MD5 hash algorithm. (3) Data encryption: To produce a digital envelope containing the encrypted image hash value (digital signature) and corresponding patient information. (4) Data embedding: To embed the digital envelope into the image. This is done by replacing the least significant bit of a random pixel of the mammogram by one bit of the digital envelope bit stream and repeating for all bits in the bit stream. Experiments with digital IMs demonstrate the following. (1) In the expert center, only the user who knows the private key ran open the digital envelope and read the patient information data and the digital signature of the mammogram transmitted from the examination site. (2) Data integrity can he verified by matching the image hash value decrypted from the digital signature with that computed from the transmitted image. (3) No visual quality degradation is detected in the embedded image compared with the original. The authors' preliminary results demonstrate that AIDM is an effective method for image authenticity and integrity in telemammography application.
Keywords: Breast pixels segmentation; Digital mammography images; Digital signature; Encrypted image hash value; Image authenticity; Image integrity; Image preprocessing; Medical diagnostic imaging; Network access issue; Patient information extraction; Privacy; Random pixel; Telemammography